Intradural Extramedullary Plasmacytoma in a Dog - Fayad Milken, Vanessa Martins; Cursino, Lilian Hilario; Menegon, Fernanda Gabriela; Parisi, Gustavo Gonçalves; Braga, Karina Michele; Medeiros-Ronchi, Alessandra Aparecida (Acta Scientiae Veterinariae, 2020)
Background: Plasmacytoma is a neoplasm originating in plasma cells, derived from B lymphocytes. Extramedullary presentation is the most common form of plasmacytoma, mainly in the skin and rarely in other tissues, including the vertebral canal. Extramedullary plasmacytoma (EMP) occurs more frequently in senile dogs and rarely in cats and some dog breeds have predisposition for this type of neoplasm. The aim of this study was to report plasmacytoma in a dog located adjacent to the thoracic vertebrae. Case: An approximately 5-year-old mongrel male with sudden paraplegia resulting from upper motor neuron injury was admitted to a University Hospital. The dog presented a six-centimeter diameter mass in the dorsal region, adjacent to the thoracic vertebrae. The leucogram presented mild leukopenia by eosinopenia and lymphopenia. Myelogram associated with epidurography showed a fill failure in the contrast column between the seventh and ninth thoracic vertebrae, and there were no osteolysis points in the thoracic vertebrae, adjacent to the neoplastic mass. The evaluation of the intervertebral spaces between the fourth to ninth thoracic vertebrae presented no increase in radiopacity, nor alterations in the size of intervertebral spaces, indicating intervertebral disc extrusion. The laterolateral radiographs showed an alignment of the vertebrae and vertebral canal, without presence of bone neoformations on the ventral face of the vertebral bodies. The animal was euthanized and fragments of mass were collected for histological analysis. Macroscopic findings presented a non-encapsulated well-delimited mass, with color ranging from white to reddish. Microscopically, there was proliferation of moderately differentiated round cells in bone and muscle tissues, arranged in mantle, with moderately eosinophilic cytoplasm, and rounded nucleus with eccentric location, coarse chromatin sometimes indistinct. These cells presented moderate anisocytosis and, in general, one mitosis per field. Intradural extramedullary plasmacytoma was diagnosed. Discussion: The present report presented a diagnosis of intradural EMP, generating compression of the spinal cord because of its invasive growth, reaching the canal and, thus, reducing its lumen. The clinical status of the dog was compatible with thoracolumbar lesion of upper motor neuron, which causes paresis and ataxia in pelvic limbs. In this case, it was not possible to establish early diagnosis because the dog had been rescued from the streets recently. Radiographic examination was important to identify the real size of the mass, and the myelography confirmed spinal cord compression. The definitive diagnosis was obtained by histological examination. Although extramedullary plasmacytoma is a low-frequency neoplasm, in the present report, its manifestation was atypical, more aggressive, invading the medullary canal and compressing the spinal cord. Spinal cord compression may lead to degeneration of axons because of alterations in the vascular permeability associated with local inflammatory process, reducing the oxygen supply to nervous tissues, resulting in cellular degeneration. The occurrence of atypical neoplastic growth should be included as a differential diagnosis for lesions in upper motor neuron in cases of spinal cord compression. This is an atypical location for this kind of neoplasia, and cases of medullary compression of neoplastic masses should be included as a differential diagnosis.